Pengaruh Trading Volume Dan Harga Saham Terhadap Return Saham Pada Perusahaan Sub Sektor Farmasi Di BEI - Mexano Hans Gery (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
The purpose of this study was to see the effect of trading volume and stock prices on stock returns in pharmaceutical sub-sector companies on the IDX. Trading volume is something that is well-known and much loved by young people who have technological skills in the hope of obtaining maximum profits, over time trading is a source of livelihood, not a few who experience profits and not a few who experience losses and even bankruptcy. This study uses pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The population in this study are all pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange 2017-2021, totaling 10 companies. Samples were taken using a purposive sampling technique, amounting to 10 companies. The data analysis technique uses multiple linear regression with a significance level of 0.05. Data processing was carried out using the computer program SPSS 22 for windows. The results of this study found that both variables partially and simultaneously have a significant effect on stock returns. With a sig level below 0.05. The contribution of the two variables trading volume and stock price is 53.3%, while the remaining 46.7% is influenced by other factors not discussed in this study.